2022
DOI: 10.1186/s13027-022-00432-4
|View full text |Cite
|
Sign up to set email alerts
|

Rat bone marrow mesenchymal stem cells (BMSCs) inhibit liver fibrosis by activating GSK3β and inhibiting the Wnt3a/β-catenin pathway

Abstract: Background Bone marrow mesenchymal stem cells (BMSCs) can effectively alleviate liver fibrosis, which is a pathological injury caused by various chronic liver diseases. This study aimed to investigate the antifibrotic effects of BMSCs and elucidate the underlying mechanism by which BMSCs affect liver fibrosis in vitro and in vivo. Methods After the rat liver fibrosis model was induced by continuous injection of carbon tetrachloride (CCl4), BMSCs we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As the end stage of liver fibrosis, cirrhosis is also involved in the Wnt/β-Catenin pathway. It has been reported that rat BMSCs alleviate liver fibrosis by inhibiting the Wnt/β-Catenin pathway [ 33 ]. In this study, we used allogeneic mouse BMSCs to treat liver cirrhosis in mice and verified the downregulation of Wnt/β-Catenin protein expression after BMSCs treatment in vivo and in vitro, thus confirming that BMSCs can alleviate the progression of liver cirrhosis through the Wnt/β-Catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As the end stage of liver fibrosis, cirrhosis is also involved in the Wnt/β-Catenin pathway. It has been reported that rat BMSCs alleviate liver fibrosis by inhibiting the Wnt/β-Catenin pathway [ 33 ]. In this study, we used allogeneic mouse BMSCs to treat liver cirrhosis in mice and verified the downregulation of Wnt/β-Catenin protein expression after BMSCs treatment in vivo and in vitro, thus confirming that BMSCs can alleviate the progression of liver cirrhosis through the Wnt/β-Catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The YTHDF2 could catch eIF4G1 transcripts with m6A methylation, and may induce the mRNA degradation, thereby promoting autophagy [ 76 ]. In addition, the m6A modification could also enhance the stability of zinc finger NFX1-type containing 1 (ZNFX1) antisense RNA 1 (ZFAS1) [ 77 ]. In more detail, for neural cells, the lnc RNA of ZFAS1 is upregulated in neural progenitor cells [ 77 ], which could regulate the expression of ATG10, and control the autophagy by preventing the PI3K/AKT pathway from stimulating the migration and/or proliferation of neural progenitor cells [ 77 ].…”
Section: M6a Rna Modifications In Autophagymentioning
confidence: 99%
“…In addition, the m6A modification could also enhance the stability of zinc finger NFX1-type containing 1 (ZNFX1) antisense RNA 1 (ZFAS1) [ 77 ]. In more detail, for neural cells, the lnc RNA of ZFAS1 is upregulated in neural progenitor cells [ 77 ], which could regulate the expression of ATG10, and control the autophagy by preventing the PI3K/AKT pathway from stimulating the migration and/or proliferation of neural progenitor cells [ 77 ]. Similarly, the YTHDF1 could enhance the translation of ATG2A and ATG14 autophagy-related genes by binding to the m6A-modified mRNA of ATG2A and ATG14, consequently assisting autophagy [ 78 ].…”
Section: M6a Rna Modifications In Autophagymentioning
confidence: 99%